2016
DOI: 10.1038/srep27590
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose and ABA regulate starch biosynthesis in maize through a novel transcription factor, ZmEREB156

Abstract: Sucrose is not only the carbon source for starch synthesis, but also a signal molecule. Alone or in coordination with ABA, it can regulate the expression of genes involved in starch synthesis. To investigate the molecular mechanisms underlying this effect, maize endosperms were collected from Zea mays L. B73 inbred line 10 d after pollination and treated with sucrose, ABA, or sucrose plus ABA at 28 °C in the dark for 24 h. RNA-sequence analysis of the maize endosperm transcriptome revealed 47 candidate transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 54 publications
1
59
0
Order By: Relevance
“…On the other hand, thus far there have been only a few reports regarding transcriptional regulation of starch synthesis in cereals. Among them, one barley WRKY transcription factor, SUSIBA2, and three maize transcription factors, ZmNAC36, ZmbZIP91, and ZmEREB156, are thought to regulate the expression of starch-synthetic genes based on transcriptional activation and/or EMSA assays of their promoters (22)(23)(24)(25). Recently, a study in rice showed that OsbZIP58, the closest homologous protein of maize O2, regulates the expression of multiple genes in the starch biosynthetic pathways, and its null mutants cause abnormal seed morphology with decreased amounts of seed starch (26).…”
Section: Significancementioning
confidence: 99%
“…On the other hand, thus far there have been only a few reports regarding transcriptional regulation of starch synthesis in cereals. Among them, one barley WRKY transcription factor, SUSIBA2, and three maize transcription factors, ZmNAC36, ZmbZIP91, and ZmEREB156, are thought to regulate the expression of starch-synthetic genes based on transcriptional activation and/or EMSA assays of their promoters (22)(23)(24)(25). Recently, a study in rice showed that OsbZIP58, the closest homologous protein of maize O2, regulates the expression of multiple genes in the starch biosynthetic pathways, and its null mutants cause abnormal seed morphology with decreased amounts of seed starch (26).…”
Section: Significancementioning
confidence: 99%
“…Both MYB and NAC homologs in Arabidopsis and maize regulate secondary cell wall deposition and components (Zhong et al, 2008(Zhong et al, , 2011. Their homologs in maize also affect starch metabolism in endosperm (Huang et al, 2016). Furthermore, several candidate genes involved in metabolism were introgressed and associated with the T6P signal in R9188/ BTx406.…”
Section: Candidate Genes Regulating T6p Pathwaymentioning
confidence: 99%
“…The previous studies also tried to identify TFs regulating synthetic starch genes by coexpression analysis and biochemistry experiments, like the Electrophoretic Mobility Shift Assay (EMSA) and the Dual-Luciferase Reporter (DLR) assay. There have been candidate TFs, including one barley WRKY transcription factor of SUSIBA2, and three maize transcription factors of ZmNAC36, ZmbZIP91, and ZmEREB156, although their regulatory function on starch synthesis remains to be validated (20)(21)(22)(23).…”
mentioning
confidence: 99%